2016
DOI: 10.1136/bjophthalmol-2014-306078
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of retinal vascular calibre and diabetic retinopathy in Chinese patients with type 2 diabetes mellitus: the Desheng Diabetic Eye Study

Abstract: In the current study, wider venular calibre, but not arteriolar calibre, was shown to be associated with development and increased severity of DR independently from other risk factors in a Chinese diabetic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
2
15
1
1
Order By: Relevance
“…Nonetheless, the experiments showed that the vascular geometry is indeed affected during the progression of diabetes, which is more or less in line with some of the previous findings [2,17,70]. The vessel widths, FD, venular angle to BC ratio, CRVE and CRAE were found to be important discriminative features of progression to DR. CRVE and CRAE observations are in line with the findings of Klein [71] and partly with [14,72,73]. These observations are linked possibly to the endothelial dysfunction, inflammatory changes, and hyperglycemia, all of which are factors involved in the pathogenesis of DR [74,75].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Nonetheless, the experiments showed that the vascular geometry is indeed affected during the progression of diabetes, which is more or less in line with some of the previous findings [2,17,70]. The vessel widths, FD, venular angle to BC ratio, CRVE and CRAE were found to be important discriminative features of progression to DR. CRVE and CRAE observations are in line with the findings of Klein [71] and partly with [14,72,73]. These observations are linked possibly to the endothelial dysfunction, inflammatory changes, and hyperglycemia, all of which are factors involved in the pathogenesis of DR [74,75].…”
Section: Discussionsupporting
confidence: 75%
“…Regarding the studies about retinal diseases, there are many that have focused on finding associations between vascular changes and retinal diseases, investigating features, such as vessels widths and angles [14,2], fractal dimension (FD) [15], tortuosity [16], arteriovenous ratio (AVR) [17], haemodynamic features [18,19], etc. However, no previous studies exist -to the extent the present work doesthat investigate at the same time and in multiple experimental designs (for validation and comparison purposes) many candidate features, by not only using proper statistical methods but also building multiple classification models.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…As mentioned previously, numerous studies have shown that the retinal vasculature changes during the progression of diabetes and DR [8,29,30,31,32].Therefore, in order to improve the accuracy of the estimation of the trunk for both arteries and veins, different data for healthy, diabetics with no-DR and DR subjects were used. All of the individuals in the diabetic and DR groups had no history of hypertension or any other cardiovascular disease.…”
Section: Data Collectionmentioning
confidence: 99%
“…Vision‐related health is always a major concern among patients with T2DM in clinics and communities. Many of the current studies on diabetes populations have focused on major vision‐threatening complications such as retinal diseases or cataracts . Epidemiologic data regarding other vision disorders such as refractive errors among individuals with T2DM are limited.…”
mentioning
confidence: 99%